Configurational theory and methods in organizational research - Fiss, Peer C.; Cambré, Bart; Marx, Axel (Research in the sociology of organizations ;, 2013)
Some 20 years after the emergence of configurational theory as a key perspective in organization studies in the 1990s, this approach has yet to deliver on its promise. While we know that configurations the relative arrangement of parts and elements - matters, empirical research on configurations is just beginning to deliver on its promise.